Shipping Decarbonization: An Overview of the Different Stern Hydrodynamic Energy Saving Devices - Flaminia Spinelli; Simone Mancini; Luigi Vitiello; Rasul Niazmand Bilandi; Maria De Carlini (Journal of Marine Science and Engineering, 2022)
In recent years, research into ships has focused on reducing emissions, consuming less energy, and being more efficient. As a result, the maritime industry has been continuing in a green and sustainable direction. Improving the fuel efficiency of ships and the decarbonization of shipping are important issues to reduce fuel consumption and emitted Greenhouse Gas (GHG) amounts. Decarbonization in the shipping industry could be achieved through technical and operational strategies such as Energy Saving Devices (ESDs) to reduce the fuel consumption of new and existing ships. According to the makers, ESDs can optimize fuel efficiency by up to 15%. This paper reviews the current literature on stern hydrodynamic ESDs, which are mainly used on typical merchant vessels, i.e., bulkers, tankers, and carriers. A comprehensive review is carried out analysing the different available solutions for stern hydrodynamic ESDs, the working principles, the methods used for the design, optimization, and evaluation of the performance improvements, and the relevant issues of these specific ESDs.